2019
DOI: 10.1371/journal.pone.0221873
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing mild cognitive impairment from healthy aging and Alzheimer’s Disease: The contribution of the INECO Frontal Screening (IFS)

Abstract: Executive functions are affected differently in healthy aging, Mild Cognitive Impairment (MCI) and Alzheimer’s Disease (AD), and evaluating them is important for differential diagnosis. The INECO Frontal Screening (IFS) is a brief neuropsychological screening tool, developed to assess executive dysfunction in neurodegenerative disorders. Goals: We aimed to examine whether and how MCI patients can be differentiated from cognitively healthy controls (HC) and mild to moderate AD patients based on IFS performance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 72 publications
1
23
0
Order By: Relevance
“…Education improved performance curvilinearly on M-WCST Categories, Perseverative errors, Total errors, and Stroop Word, and linearly on Stroop Color and Word-Color. This is consistent with prior studies that showed improved executive functions with higher levels of education (Llinas-Regla, Vilalta-Franch, Lopez-Pousa, Calvo-Perxas, & Garre-Olmo, 2013;Moreira et al, 2014;Moreira et al, 2019;Pavão Martins, Maruta, Freitas, & Mares, 2013). Higher education levels appear to contribute to cognitive reserve, behaving as a neuroprotector factor on the decline associated with healthy aging in EF (Roldán-Tapia, Cánovas, León, & García-Garcia, 2017; Thow et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Education improved performance curvilinearly on M-WCST Categories, Perseverative errors, Total errors, and Stroop Word, and linearly on Stroop Color and Word-Color. This is consistent with prior studies that showed improved executive functions with higher levels of education (Llinas-Regla, Vilalta-Franch, Lopez-Pousa, Calvo-Perxas, & Garre-Olmo, 2013;Moreira et al, 2014;Moreira et al, 2019;Pavão Martins, Maruta, Freitas, & Mares, 2013). Higher education levels appear to contribute to cognitive reserve, behaving as a neuroprotector factor on the decline associated with healthy aging in EF (Roldán-Tapia, Cánovas, León, & García-Garcia, 2017; Thow et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Executive and attentional dysfunction are common in a wide variety of conditions including acquired brain injury (e.g., TBI: Caeyenberghs et al, 2014;Cicerone & Giacino, 1992;McDonald, Flashman, & Saykin, 2002;Shah et al, 2017;Tramontana, Cowan, Zald, Prokop, & Guillamondegui, 2014), stroke (Olgiati, Russell, Soto, & Malhotra, 2016;Pohjasvaara et al, 2002;Vataja et al, 2003), neuropsychiatric (e.g., bipolar depression: Caixeta et al, 2017;and schizophrenia: Carter et al, 2010;Dirnberger, Fuller, Frith, & Jahanshahi, 2014;Gavilán & García-Albea, 2015), neurodegenerative (e.g., Alzheimer's disease: Amiéva et al, 2004;Binetti et al, 1996;Firbank et al, 2016;Moreira, Lima, Vicente, 2014;Moreira, Costa, Machado, Castro, Lima, & Vicente, 2019;Swanberg, Tractenberg, Mohs, Thal, & Cummings, 2004; the behavioral-variant frontotemporal dementia, bvFTD: Fiorentino et al, 2013;Slachevsky et al, 2004;and Parkinson's: Dirnberger & Jahanshahi, 2013;Lima, Meireles, Fonseca, Castro, & Garret, 2008;Papagno & Trojano, 2018;Zgaljardic et al, 2006), and neurodevelopmental disorders (e.g., ADHD: Kingdon, Cardoso, & McGrath, 2016;Margari et al, 2016;Veloso, Vicente, & Filipe, 2020;and autism: Filipe, Frota, & Vicente, 2019;Miller & Hinshaw, 2015), among many others conditions.…”
Section: Introductionmentioning
confidence: 99%
“…MCI is a stage between the normal CD of aging and dementia; patients with memory and executive function deterioration have a high risk of progressing to dementia. 9 American Association of Neurology (AAN) states the progression to dementia in those older than 65 years with MCI is 14.9%, and the risk of MCI increases with age. 9 Patients with MCI may progress to dementia, remain stable, or return to a neurologically intact status.…”
Section: Mild Cognitive Impairmentmentioning
confidence: 99%
“…9 American Association of Neurology (AAN) states the progression to dementia in those older than 65 years with MCI is 14.9%, and the risk of MCI increases with age. 9 Patients with MCI may progress to dementia, remain stable, or return to a neurologically intact status. 9 There are no evidence-based studies indicating that pharmacologic therapies for MCI are effective.…”
Section: Mild Cognitive Impairmentmentioning
confidence: 99%
See 1 more Smart Citation